The Relationship Between Psychological Hardiness and Mindfulness in University Students: The Role of Spiritual Well-Being - Betül Yavuz; Bülent Dilmaç (Spiritual Psychology and Counseling)
The purpose of the research is to reveal the role of spiritual well-being in relationship between psychological hardiness and mindfulness in university students. The sample of the research consisted of a total of 561 university students with convenience sampling strategy who were between 17-49 years of age and were studying in Konya 2017 and 2018. The research is done in accord with relational scanning which is a subgenre of general survey model. In this research structural equation modeling analysis has been applied to test the relationships among psychological hardiness, mindfulness and spiritual well-being variables of university students. Structural equation modeling analysis has been carried out using AMOS 19 software. In the study, ‘Demographic Information Form’, ‘The Psychological Hardiness Scale’, ‘Five Facets Mindfulness Questionnaire’ and ‘Spiritual Well-Being Scale’ were used. According to the findings obtained from the research, the major independent variable which affects the psychological hardiness of university students was mindfulness. A significant positive correlation was found between mindfulness levels and psychological hardiness levels. It is also observed that there is a positive linear correlation between spiritual well-being and psychological hardiness and mindfulness.